An introduction to rights - Edmundson, William A. (William Atkins), 1948- (New York : Cambridge University Press, 2012)
"A thoroughly updated second edition that is an accessible introduction to the history, logic, moral implications, and political tendencies of the idea of rights"--
Machine generated contents note: Part I. The First Expansionary Era: 1. The prehistory of rights; 2. The rights of man: the enlightenment; 3. Mischievous nonsense?; 4. The nineteenth century: consolidation and retrenchment; 5. The conceptual neighborhood of rights: Wesley Newcomb Hohfeld; Part II. The Second Expansionary Era: 6. The universal declaration, and a revolt against utilitarianism; 7. The nature of rights: 'choice' theory and 'interest' theory; 8. A right to do wrong? two conceptions of moral rights; 9. The pressure of consequentialism; 10. What is interference?; 11. The future of rights; 12. Conclusion.
Includes bibliographical references and index.
Keywords: Civil rights; Human rights